The Competency-based Approach in Higher Education - Saliha, Chelli (Sciences humaines; Vol. 22 (2011): SCIENCES HUMAINES)
In spite of the reform undergone in  higher education in Algeria, there is no real change in English language teaching. But if we examine the changes in other countries including European ones, we shall find that the competency-based approach causes a lot of interest among practitioners of higher education.           This paper aims to show that the competency-based approach, as an approach based on socio-constructivism which provides a shift from the traditional focus on teacher-centred delivery to learning outcomes and learner-centred educational objectives, is appropriate to the purposes of the reform and to the new demands of life including job requirements.   رغم الإصلاحات التربوية التي تمت على مستوى التعليم العالي، لم يلاحظ أي تغيير في ما يخص تدريس اللغة الانجليزية، بل لو نرجع للتغيير في البلدان الأخرى على سبيل المثال في الدول الأوربية نجد أن منهج المقاربة بالكفاءات  يلقى اهتماما كبيرا من طرف الأساتذة والباحثين في التعليم العالي .      يهدف هذا المقال إلى إظهار مدى صلاحية وملاءمة منهج المقاربة بالكفاءات للتعليم العالي كونه يمثل منهجا يعتمد على التركيز على تكوين المتعلم في الحياة العصرية وزمن العولمة ومن بينها مجال الشغل بدلا من التعليم التقليدي الذي يعتمد على التلقين.